The Role of Advertising Exposure to Consumer Purchase Interest: Study of Gain Mass Milk Ads in Fitness Center - Septian, Muhammd Rio; Alfatih, Andy; Meilinda, Nurly (Open Access Indonesia Journal of Social Sciences, 2018)
Today, every day the community is always crammed with so many advertisements that offer various conveniences. For some advertisers, advertising through electronic media (television) becomes an attractive alternative choice, in addition to its wide reach, ad serving through television media can reach a broad target. This study has two problem formulations namely whether there was an influence of exposure milk advertising on consumer buying interest. Meanwhile, the data analysis techniques in this study were quantitative descriptive techniques and explanative techniques. This research was conducted with a sample of 60 respondents, namely members of AA 'Gym Fitness Club Indralaya in 2017 and conducted between March and June 2018. The data were collected via distributing questionnaires, observations, and documentation. Based on data analysis, the results show that gain mass milk advertisement had a significant influence on consumers' buying interest because in this study based on t value it is known that the t-count value is 3.081> ttable 2.002 so it can be concluded that the ad exposure variable influences the consumer purchase interest variable. Thus H1 is accepted and H0 is rejected. In this study, it also obtained an R Square value of 0.141. So it can be interpreted that the independent variable X (exposure to advertising) has a contribution of 14.1% to the variable Y (consumer buying interest).